2010
DOI: 10.1542/peds.2009-2218
|View full text |Cite
|
Sign up to set email alerts
|

High or Low Oxygen Saturation and Severe Retinopathy of Prematurity: A Meta-analysis

Abstract: CONTEXT Low oxygen saturation appears to decrease the risk of severe retinopathy of prematurity (ROP) in preterm newborns when administered during the first few weeks after birth. High oxygen saturation seems to reduce the risk at later postmenstrual ages (PMAs). However, previous clinical studies are not conclusive individually. OBJECTIVE To perform a systematic review and meta-analysis to report the association between severe ROP incidence of premature infants with high or low target oxygen saturation meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
108
2
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 152 publications
(117 citation statements)
references
References 59 publications
3
108
2
4
Order By: Relevance
“…Their study showed that the rate and severity of ROP increased especially amongst extremely preterm infants after adopting a higher SpO 2 target (91-95%) with no concomitant reduction in mortality but the study was underpowered for this outcome (29). Based on the pathophysiology of ROP, studies were designed to address the issue of using a higher SpO 2 target at 32 wk PMA which resulted in reduced progression to severe ROP (30). We implemented graded SpO 2 targets in 2002, mimicking oxygen delivery: oxygen consumption ratios during fetal life.…”
Section: Discussionmentioning
confidence: 99%
“…Their study showed that the rate and severity of ROP increased especially amongst extremely preterm infants after adopting a higher SpO 2 target (91-95%) with no concomitant reduction in mortality but the study was underpowered for this outcome (29). Based on the pathophysiology of ROP, studies were designed to address the issue of using a higher SpO 2 target at 32 wk PMA which resulted in reduced progression to severe ROP (30). We implemented graded SpO 2 targets in 2002, mimicking oxygen delivery: oxygen consumption ratios during fetal life.…”
Section: Discussionmentioning
confidence: 99%
“…Recently published studies recommend the use of supplementary oxygen in premature babies with gestation ≥32 GW during the first few weeks of life, with lower oxygen saturation (85-93%), whilst later than ≥32 GW they should have higher oxygen saturation (94-99%). This approach to treatment with oxygen is accompanied by a reduction in the risk of occurrence of severe forms of ROP (23,26).…”
Section: Discussionmentioning
confidence: 99%
“…20 A meta-analysis of the association between SaO 2 measured by pulse oximetry and risk of severe ROP indicated a statistically significant risk reduction of 52% with low SaO 2 (70 -96%) in the first postnatal weeks and 46% with high SaO 2 (>94 -99%) at a postmenstrual age (PMA) of ≥32 weeks. 21 The analysis revealed that high SaO 2 has different effects at postnatal points that correspond roughly to the first and second phases of ROP.…”
Section: Oxygen Saturation Guideline After Birthmentioning
confidence: 96%
“…In a meta-analysis of high or low oxygen saturation and severe ROP, Chen et al 21 concluded that low SaO 2 (70 -96%) in the first several postnatal weeks was associated with a reduced risk of severe ROP (RR 0.48; 95% CI 0.31 -0.75) and high SaO 2 (94 -99%) after a PMA of 32 weeks was associated with a decreased risk for progression to severe ROP (RR 0.54; 95% CI 0.35 -0.82). 21 Currently, the ongoing Neonatal Oxygen Prospective Metaanalysis (NeOProM) study is questioning whether targeting a lower oxygen range in extremely premature neonates increases or decreases the composite outcome of death or major disability in survivors by ≥4%.The results of the study will be available in 2014.…”
Section: Oxygen Saturation Guideline After Birthmentioning
confidence: 99%